2001
DOI: 10.1080/03075070123233
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Information and Communication Technologies in a University Learning Environment

Abstract: This article reports three related studies which investigate how undergraduates use and think about information and communication technologies (ICT) in the context of learning at university. Data were obtained via questionnaires, computer diary records and focus group discussions. The studies were intended to help universities decide how to incorporate ICT into student learning, how the cost of equipment should be shared between students and institutions, and how university provision should be organised to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(23 citation statements)
references
References 7 publications
0
23
0
Order By: Relevance
“…Despite huge efforts to position computer technology as a central tenet of university education, the fact that many students and faculty make only limited formal academic use of ICT during their teaching and learning is less discussed by educational technologists. Belying the notion of the ‘cyber‐campus’, the actual formal use of new technologies in undergraduate and graduate studies remains inconsistent and highly variable from course to course and institution to institution (Breen et al . 2001; Marriott et al .…”
Section: Introductionmentioning
confidence: 99%
“…Despite huge efforts to position computer technology as a central tenet of university education, the fact that many students and faculty make only limited formal academic use of ICT during their teaching and learning is less discussed by educational technologists. Belying the notion of the ‘cyber‐campus’, the actual formal use of new technologies in undergraduate and graduate studies remains inconsistent and highly variable from course to course and institution to institution (Breen et al . 2001; Marriott et al .…”
Section: Introductionmentioning
confidence: 99%
“…Within Breen et al . 's () attributes for evaluating technological tools in university technology‐based learning environments, information overload refers to the belief or judgement that learning is impaired by the quantity of the irrelevant material. In other words, a well‐structured, operated and maintained digital learning environment, such as the blog, which is often updated with acceptable quality material, increases the students' engagement.…”
Section: Statistical Evaluation Of the Methodologymentioning
confidence: 99%
“…Additionally, researchers have noted that instructors who adopt technology in their classrooms typically do not change their teaching styles to incorporate the collaborative potential of these technologies (Grasha & YangarberHicks, 2000). Breen (2001) has found that the use of technology in higher education classrooms is highly variable across institutions and classrooms within institutions. In our case, further investigation into how this technology was implemented was needed to further interpret our results.…”
Section: Discussionmentioning
confidence: 99%